Q. 45.0( 5 Votes )

If nth term of an

Answer :

Given: nth term of an A.P. is (2n + 1),


To find: the sum of its first three terms


Explanation: given nth term of an A.P. is (2n + 1),


an = 2n + 1……….(i)


Now the first term of the AP can be found by substituting n = 1, so we get


a1 = 2 × 1 + 1


= 2 + 1


a1 = 3………(ii)


Now the second term of the AP can be found by substituting n = 2, so we get


a2 = 2 × 2 + 1


= 4 + 1


a2 = 5………(iii)


Now the third term of the AP can be found by substituting n = 3, so we get


a3 = 2 × 3 + 1


= 6 + 1


a3 = 7………(iv)


So, the sum of the first three terms of the AP is


a1 + a2 + a3


Now substituting values from equation (ii), (iii) and (iv) we get


a1 + a2 + a3 = 3 + 5 + 7


= 15


Hence the sum of its first three terms is 15.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses